Premature Ovarian Insufficiency and Long-Term Health Consequences - Tsiligiannis, Sophia; Panay, Nick; Stevenson, John C. (Current Vascular Pharmacology, 2019)
Premature ovarian insufficiency (POI) is defined as the cessation of ovarian function before the age of 40 years. The trio of amenorrhea, elevated gonadotropins and oestrogen deficiency is associated with long-term health consequences including increased cardiovascular disease (CVD), decreased bone mineral density (BMD), significantly reduced fertility, psychological distress, vulvovaginal atrophy, neurological effects and overall reduced life expectancy. There are deficits in our understanding of this condition and subsequently the long-term health consequences. The underlying aetiology of POI and the optimal management strategies are also poorly understood. Our knowledge of long-term cardiovascular consequences specifically relating to women with POI is limited as most data on the subject are derived from studies involving women who experienced menopause at the natural age (after 40 years with an average age of 51).
Keywords: cardiovascular disease